A green approach of preparation of fine active alumina with high specific surface area from sodium aluminate solution. Issue 10 (14th February 2019) - Wu, Guoyu; Liu, Guihua; Li, Xiaobin; Peng, Zhihong; Zhou, Qiusheng; Qi, Tiangui
Abstract : A green preparation of fine active alumina from saturated sodium aluminate solution by phase evolution is presented. High capillary pressure, numerous mesopores, and the inhibition of aggregation produced FAA with an extremely high specific surface area. Abstract : Fine active alumina (FAA) with a high specific surface area (SSA) is used in catalysis, adsorbents and other applications. This study presents a novel method of preparing high surface area FAA via a phase evolution from gibbsite through ammonium aluminum carbonate hydroxide (AACH) to FAA. Thermodynamic calculations showed that increasing the pH and (NH4 )2 CO3 concentration both promoted the transformation of gibbsite to AACH. Fine gibbsite precipitated from a sodium aluminate solution could thus be efficiently changed to AACH and subsequently to FAA. Minimal particle aggregation was achieved from gibbsite to AACH to FAA owing to the filling of capillaries by NH3 and CO2, the formation of boehmite and interfacial hydrophobicity. Furthermore, capillary pressures of 1.25–46.56 MPa during the AACH roasting process prevented the collapse of mesopores. The high capillary pressure, numerous open mesopores, and inhibition of aggregation produced FAA with an extremely high SSA. The SSA of FAA was as high as 1088.72 m 2 g −1 following the roasting of AACH at 300 °C for 180 min. This FAA was demonstrated to remove phosphate from wastewater with an adsorption capacity of 300.28 mg g −1 .